The influence of the scout upon the decision-making process of recruited workers in three Acromyrmex species (Formicidae : Attini) - Lopes, JFS; Orti, LCF; Camargo, R. S. (Elsevier B.V., 2004)
We examined how the information communicated by a scout worker influences the plant species transported by recruited workers in Acromymex balzani, Acromyrmex rugosus, and Acromyrmex crassispinus, three species of leaf-cutting ant that have different substrate and habitat preferences. We verified that certain plant species were more likely to be transported than others and that recruitment occurs. We found that recruited workers were more likely to transport non-preferred plant species when they were recruited to these by scout workers. The results suggest that the scout worker can communicate information about plant identity to recruited workers, but that recruited workers integrate the information communicated with their own experience during the decision-making process. (C) 2004 Published by Elsevier B.V.
Keywords: Acromyrmex; decision-making; foraging; leaf-cutting ants; recruitment